Forty years of silvicultural management in southern Nothofagus pumilio primary forests. - Gea Izquierdo, Guillermo (2004)
To achieve sustainability of a forest system it is necessary to apply appropriate silvicultural management, includingpreservation measures. The characterization of the status and development of the harvested stands, as well as the timber potentialof the unmanaged ones, is necessary to achieve a sustainable forest management. In southern Patagonia, Nothofagus forests arethe basis for the sawmill industry. Since European colonization, different silvicultural management regimes have been applied inprimary forests. Forestry policies and available sawmill technologies have also been involved. There is little knowledge aboutthe consequences of the different silvicultural systems implemented, as well as about the regeneration status of the harvestedstands and future possibilities of the managed forests. The objective of this work is to analyse the logged, affected fromharvesting and current forest structures, as well as the regeneration development during the last 40 years and the consequencesderived to forests of southern Patagonia.The harvesting was applied irregularly between the studied decades (30 15% of the original basal area was removed)creating an irregular forest structure. Large quantities of sawn logs were abandoned in the forest floor and a high percentage ofthe remaining forest structure was damaged during the harvesting. Negligent management and wind throw produced a hugeamount of wasted timber, resulting in a scarce standing log volume of very low quality. Nevertheless, regeneration wassuccessfully installed (222 185 thousands/ha) within the harvested stands. No differences in the harvesting intensity werefound with the different theoretical silvicultural methods applied through the years (selective cuts, clear-cuts or shelterwoodcuts). As a result, the forests present a low current and future economical potential. Hence, the status of the secondary forest mustbe improved and regulated in order to achieve sustainability. Otherwise, the local forest industry will suffer from negativeconsequences, and this valuable resource will not be profitable in the future.